ENGLISH AS A SECOND LANGUAGE - Karimova Oydinoy; Baltabayeva Nargiza (Journal of new century innovations, 2023)
Abstract: this article discusses the importance of English as a second language (ESL) instruction in today's globalized world. The article explains why people choose to learn English, the benefits of learning a second language, and various ESL teaching techniques. It also highlights the challenges that students may face and emphasizes the importance of providing effective support and resources to help them succeed. Overall, the article stresses the importance of ESL instruction in helping individuals communicate effectively, improve their job opportunities and earning potential, and enhance their cognitive function